2022
DOI: 10.53730/ijhs.v6ns9.13667
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional evaluation of maxillary sinus volume following the use of different designs of rapid maxillary expander

Abstract: Aim of the study: to assess maxillary sinus volume changes (MSV) in adolescent patients with class III malocclusion after application of three types of rapid maxillary expanders (RME). Material and Methods: This was a prospective cohort study that recruited adolescent (13-17 years old) class III malocclusion patients with maxillary deficiency. Patients were randomly assigned to three study groups according to the type of RME: Conventional hyrax (CH), hybrid hyrax (HH), and maxillary skeletal expanders (MSE). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…24 Similarly, Shendy et al reported a significant increase in maxillary sinus volume following RPE regardless the type of maxillary expander used. 25 The results of our study, which is the only one available for patients with UCLP, did not find any additional statistically significant effect for maxillary expansion on the maxillary sinus volume.…”
Section: Discussionmentioning
confidence: 43%
“…24 Similarly, Shendy et al reported a significant increase in maxillary sinus volume following RPE regardless the type of maxillary expander used. 25 The results of our study, which is the only one available for patients with UCLP, did not find any additional statistically significant effect for maxillary expansion on the maxillary sinus volume.…”
Section: Discussionmentioning
confidence: 43%